2008
DOI: 10.2174/1874834100801010042
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of the Catalyst Support from the Oil-Shale Processing By-Product

Abstract: 5-methylresorcinol and the technical mixture of oil-shale phenolic compounds were applied for carbon aerogel preparation. Gels, which were prepared via base catalyzed polymerization were dried under supercritical conditions and subsequent pyrolysis of obtained dry aerogels led to carbon aerogels. Activation of carbon aerogel with CO 2 and H 2 O was performed and porosity and the specific surface area of activated carbon aerogels were studied. Langmuir specific surface areas of well over 2000 m 2 /g were achiev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…MR is a good alternative to resorcinol. Besides MR being a byproduct of oil shale industry and therefore a locally available precursor, gels prepared from MR have also shown faster gelation times compared to gels prepared from resorcinol [3][4][5]. The preparation of aerogels from MR and dHMBA together showed that the structure and properties of aerogels are dependent on the molar ratio of MR to dHMBA.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…MR is a good alternative to resorcinol. Besides MR being a byproduct of oil shale industry and therefore a locally available precursor, gels prepared from MR have also shown faster gelation times compared to gels prepared from resorcinol [3][4][5]. The preparation of aerogels from MR and dHMBA together showed that the structure and properties of aerogels are dependent on the molar ratio of MR to dHMBA.…”
Section: Introductionmentioning
confidence: 99%
“…Doping of carbon aerogels prepared from MR and FA with palladium by using impregnation in supercritical CO 2 has been previously carried out, but to the authors' knowledge no attempt to dope aerogels prepared from dHMBA has been made before [5].…”
Section: Introductionmentioning
confidence: 99%
“…Then, the gel was dried via supercritical carbon dioxide extraction on a 100-ml autoclave (constructed by NWA Analytische Meßgeräte GmbH) to obtain an organic aerogel. Carbon aerogel was prepared by heating the organic aerogel up to 900°C in a nitrogen flow, following a temperature programme proposed by Pérez-Caballero et al [16]. Activation of the carbon aerogel was carried out in a CO 2 flow at 900°C for 2 h with the temperature ramping rate 10°C min −1 .…”
Section: Methodsmentioning
confidence: 99%